Investigation of Women Employees in Family Health Centers of Eskişehir Province about Normal Birth and Caesarean Birth - Türkan Geçer (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2020)
Unnecessary caesarean delivery continues to be an increasingly important problem in the world. Thanks to the information and training provided with the right resources, it is possible to reduce the caesarean rates and increase the normal birth rates with the right choices. This study aimed to learn the opinions of female employees in Eskişehir family health centers about normal and caesarean births, to determine important points and develop suggestions for these methods. The population of the study was 170 working women. Factor analysis, 16 items normal birth, and caesarean delivery scale were gathered under one factor, and this single factor explained 36.775% of the total variance. Results showed that when item-total correlation values of normal birth and caesarean section were examined, it was found that item-total correlation values of 16 items in the scale were between 0.407 and 0.759. When item scores were examined, it was determined that there was consistency between the items. This research has shown that the majority of female workers prefer to giving births by caesarean section, while there is no clinical indication and they are suggested to normal delivery. As a result of the established DFA model, the fit indexes of the model were found to be among the perfect fit values (x2/df=65.26/25≤3).